EKOLOGI POLITIK DALAM PERLUASAN WILAYAH MASA SRIWIJAYA: BERDASARKAN BEBERAPA BUKTI PRASASTI - Muhamad Alnoza; Rafael Arya Bagas Ananta; Mentari Putri Ramadhanti (Balai Arkeologi Sumatera Utara, 2020)
Srivijaya is a federation state in Nusantara on the 7th century AD. Dapunta Hyang as the first of Datu Sriwijaya, was first mentioned in the Kedukan Bukit Inscription (606 AD). In its development, Srivijaya's authority which began in Palembang began to develop into the surrounding areas. Evidence of this expansion of Srivijaya is recorded in the Srivijaya inscriptions found in these areas. The inscriptions found generally contain curses about people who rebel against unity. This paper is intended to reconstruct the ecological considerations made by Srivijaya in expanding its territory. This paper connects the location of the discovery of the inscription, the composition of the contents of the curse of the inscription and number of inscriptions to find out the priority scale of the Sriwijaya territory. The analyzed data is then compare it with the ecological conditions of each region. In interpreting the expansion of the region based on ecological and geographic conditions, political ecology theory is used. Finally, it can be seen that Palembang is the axis of unity, because of the many inscriptions found and the curse composition in the inscriptions. Palembang has a wealth of natural resources and the most favorable geographical conditions for the Sriwijaya Union. The inscription discovery area outside Palembang is a hinterland area, whose natural wealth is used as a commodity for Kadatuan Sriwijaya.